2020
DOI: 10.3390/genes11090975
|View full text |Cite
|
Sign up to set email alerts
|

Snorkeling Strategy: Tolerance to Flooding in Rice and Potential Application for Weed Management

Abstract: Flooding is an important strategy for weed control in paddy rice fields. However, terrestrial weeds had evolved mechanisms of tolerance to flooding, resulting in new ‘snorkeling’ ecotypes. The aim of this review is to discuss the mechanisms of flooding tolerance in cultivated and weedy rice at different plant stages and the putative utility of this trait for weed management. Knowledge about flooding tolerance is derived primarily from crop models, mainly rice. The rice model informs us about the possible flood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Fast generation of adventitious roots may facilitate oxygen diffusion and improve aeration of flooded organs (Ayi et al, 2016;Park et al, 2020), which has been proved to be caused by ethylene accumulating because of limited gas diffusion in floodwater (Voesenek and Bailey-Serres, 2015;Herzog et al, 2016;Joshi and Ginzberg, 2021). In response to flooding, plants often prioritize activities related to survive such as aeration and nutrient absorption, with faster responses in roots than in shoots (Striker et al, 2014;Vidoz et al, 2016;Kaspary et al, 2020).…”
Section: Discussion Growth Responses Of Polygonum Hydropiper To Early...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fast generation of adventitious roots may facilitate oxygen diffusion and improve aeration of flooded organs (Ayi et al, 2016;Park et al, 2020), which has been proved to be caused by ethylene accumulating because of limited gas diffusion in floodwater (Voesenek and Bailey-Serres, 2015;Herzog et al, 2016;Joshi and Ginzberg, 2021). In response to flooding, plants often prioritize activities related to survive such as aeration and nutrient absorption, with faster responses in roots than in shoots (Striker et al, 2014;Vidoz et al, 2016;Kaspary et al, 2020).…”
Section: Discussion Growth Responses Of Polygonum Hydropiper To Early...mentioning
confidence: 99%
“…Hypoxia and low light intensity because of partial or complete coverage with water can limit photosynthesis and respiration in plants. This may result in growth retardation or even plant death (Striker et al, 2012(Striker et al, , 2014Kaspary et al, 2020;Kolton et al, 2020;Hartman et al, 2021). However, it has been shown that the stimulation of mild flooding at an early period can act as a signal and induce positive plant responses to subsequent severe flooding stress (Yin et al, 2014;Li et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Further, several major rice weeds, such as weedy rice, Echinochloa spp., Cyperus spp. or Fimbristylis miliacea, are tolerant to flooding (Kaspary et al 2020).…”
Section: Rice Weedsmentioning
confidence: 99%
“…How and why is Echinochloa crus-galli so tolerant to flooding? E. crus-galli was continuously reported as tolerant to water-based management practices in the last decades (Estioko et al 2014;Ismail et al, 2012;Peralta et al, 2019;Kaspary et al, 2020). Its ability to persist in flooded environments (Maun and Barrett, 1986;Bajwa et al, 2015) has been described in several studies (Kennedy et al, 1980;Chauhan and Johnson, 2011;Estioko et al, 2014).…”
Section: Chapter 4 Identification Of Echinochloa Crusgalli-specific F...mentioning
confidence: 99%
“…This is because of several factors including (1) manual weeding -one of the common weed control methods in smallholder farming in Asia and Africa is becoming less economically viable because of rising labour shortages and consequently wage costs (Ahmed et al 2021;Bajwa et al 2015). Moreover, E. crus-galli is phenotypically similar to rice which makes it indistinguishable from rice at the seedling stage, and hence manual weeding is extremely difficult and less effective (Barrett et al, 1983); (2) E. crus-galli has evolved resistance (cross and multiple resistance) to several commonly used herbicides in rice -making chemical weed control challenging for E. crus-galli as one of the world's most serious herbicide-resistant weeds (Heap, 2019); and (3) E. crus-galli is becoming increasingly tolerant to flooding/water-based management practice (Estioko et al 2014;Ismail et al, 2012;Peralta et al, 2019;Kaspary et al 2020). These factors warrant the need to develop alternative non-chemical weed management options for this weed species and combine them with herbicide use as an integrated weed management strategy.…”
Section: Introductionmentioning
confidence: 99%